2020
DOI: 10.1038/s41598-020-58304-z
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia index based on serum creatinine and cystatin C is associated with 3-year mortality in hospitalized older patients

Abstract: To investigate the association of the sarcopenia index (SI, serum creatinine value/cystatin C value × 100) with 3-year mortality and readmission among older inpatients, we reanalyzed a prospective study in the geriatric ward of a teaching hospital in western China. Older inpatients aged ≥ 60 years with normal kidney function were included. Survival status and readmission information were assessed annually during the 3-year follow-up. We applied Cox regression models to calculate the hazard ratio (HR) and 95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 33 publications
0
58
0
Order By: Relevance
“…Moreover, we recently found that the sarcopenia index was correlated with handgrip strength (r 2 = 0.24, p < 0.001) among older Chinese inpatients 15 . A more recent report has indicated that handgrip strength in 677 community-dwelling older Japanese adults was correlated with the Cr/CysC ratio 16 .…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, we recently found that the sarcopenia index was correlated with handgrip strength (r 2 = 0.24, p < 0.001) among older Chinese inpatients 15 . A more recent report has indicated that handgrip strength in 677 community-dwelling older Japanese adults was correlated with the Cr/CysC ratio 16 .…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, Hirai et al 71 demonstrated that the Cr/CysC may serve as a surrogate marker for sarcopenia in COPD, with a cut-off of 0.71 in male patients. However, Tang et al 72 recently suggested that the Cr/CysC ratio could only serve as a potentially valuable biomarker to predict adverse outcomes in elderly, but not necessarily as a surrogate marker for sarcopenia, since other factors, such as chronic kidney disease, 73 a frequent comorbidity in COPD patients, 74 might also influence serum Cr levels. Therefore, although serum Cr and CysC can be easily determined in clinical practice, better validation is required before this can be applied in clinical practice.…”
Section: Dovepressmentioning
confidence: 99%
“…Therefore, although serum Cr and CysC can be easily determined in clinical practice, better validation is required before this can be applied in clinical practice. 72 • In the search for reliable biomarkers to reflect muscle damage, urinary titin, a sarcomeric protein that is excreted in urine, has been investigated and was found to correlate with blood markers of muscle damage. 75 More recently, elevated levels of urinary titin were demonstrated to correlate with rectus femoris muscle atrophy in intensive care patients.…”
Section: Dovepressmentioning
confidence: 99%
“…Although there was no statistical or numerical difference in baseline serum albumin across levels of appetite in the current study, it is possible that baseline serum albumin was not sensitive enough to differentiate nutritional status, and using time‐average serum albumin may have better reflected dialysis‐associated malnutrition. Nonetheless, a progressive decrease in serum creatinine with poorer appetite suggested a higher prevalence of sarcopenia in poor appetite patients 28,29 . Given the similar body mass index, lower serum creatinine also raises the possibility of subclinical overhydration in the poor appetite group, preceding overt malnutrition 30 .…”
Section: Discussionmentioning
confidence: 99%